2021
DOI: 10.20473/jmtt.v14i2.26192
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Work Motivation, Job Satisfaction, and Employee Performance: The Moderating Role of Psychology Capital and The Mediating Role of Organizational Commitment

Abstract: This study aims to determine the effect of work motivation, organizational commitment, and job satisfaction on employee performance. The effect of organizational commitment mediates the relationship between work motivation on employee performance and job satisfaction on employee performance and psychological capital, which moderates the relationship between job satisfaction and employee performance. The object of this research is the employees of the state civil apparatus. They work in government agencies in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…The accepted hypothesis can be caused by a number of factors wrong salary received accordingly so as to make employees commit to contribute to the company. The results of this hypothesis are in line with the results of research conducted by (Astuti & Amalia, 2021) which proves organizational commitment has a positive and significant influence on mediating motivation on employee performance. According to (Maslow, 2017), the award or prestige given by the Company will make employees able to provide optimal work results and be active in all Company activities.…”
Section: Influence Between Motivation On Employee Performance Mediate...supporting
confidence: 87%
“…The accepted hypothesis can be caused by a number of factors wrong salary received accordingly so as to make employees commit to contribute to the company. The results of this hypothesis are in line with the results of research conducted by (Astuti & Amalia, 2021) which proves organizational commitment has a positive and significant influence on mediating motivation on employee performance. According to (Maslow, 2017), the award or prestige given by the Company will make employees able to provide optimal work results and be active in all Company activities.…”
Section: Influence Between Motivation On Employee Performance Mediate...supporting
confidence: 87%
“…Rahmitasari et al, (2021) found that motivation has a positive and significant effect through a commitment to inspire the same direction and goals reflected in organizational commitment, so that it impacts their better performance. This view is different from other researchers, for example, Astuti andAmalia (2021), andMasydzulhak et al (2016), that the effect of the level of work motivation on employee performance decreases. This shows that organizational commitment cannot effectively mediate work motivation on employee performance.…”
Section: Introductioncontrasting
confidence: 76%
“…Masydzulhak et al, (2016) state that employee performance increases when positive work motivation increases and is important. Astuti & Amalia, (2021) directly identify factors that affect employee performance without having to be mediated by organizational commitment owned by employees. Rahim & Jam'an, (2018) stated that motivating company employees to follow the employee's desire to grow employee commitment to the company in producing their performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between an employee and their organization is not always good or conducive to the achievement of the desired results. Job satisfaction is a key element that affects the motivation of an employee and therefore increases their level of commitment to the organization [3,4]. Organizational commitment is very important for companies [5], as it is expected to increase the productivity of employees, but it is also an opportunity for the company to reward its employees for the individual and collective effort they make in their job performance.…”
Section: Introductionmentioning
confidence: 99%